The unbearable lightness of laughting: a reflexive thematic analysis of smiles and laughter in five psychotherapy training processes - Hoff, Cecilie Hillestad; Strømme, Hanne (Frontiers in Psychology, 2025)
ObjectiveThis study explored how smiles and laughter unfolded in five psychotherapy training processes, comprising two psychodynamic, two metacognitive, and one integrative.MethodsUsing a multimodal approach, video observations from naturalistic therapy and supervision sessions served as a springboard for Interpersonal Process Recall interviews with therapists, clients, and supervisors. Transcripts from supervision sessions and interviews were analyzed with Reflexive Thematic Analysis.FindingsThe analysis yielded four themes: 1. Smiles and laughter sometimes served to strengthen the therapeutic alliance, while at other times they functioned as emotion-regulating strategies or carried profound personal significance; 2. The therapists intuitively tended to downregulate their responses to clients’ expressions of laughter, to modulate and contain the clients’ underlying emotions; 3. The way therapists handled laughter and smiles in the therapeutic setting seemed to be related to their degree of security and the quality of the therapeutic relationship; and 4. In supervision, smiles and laughter were not explicitly addressed as a distinct theme but occasionally surfaced spontaneously during sessions.ConclusionBy showing how clinical practice unfolds on observable and inferred emotional levels, the study highlights the importance of empirical grounding and the difficulty of verbalizing subtle nonverbal processes.